Development of Augmented Reality for Biology E-Magazine - Putri, Deka Gusnia; Zulfarina, Zulfarina; Syafii, Wan (FKIP-Universitas Riau, 2021)
The purpose of this research is to design an electronic magazine design so that students are interested in participating in the learning process. Many students find it difficult to understand biology concepts because they cannot see it directly. We can use Augmented Reality technology in e-magazine design as one of these innovations. Therefore, this descriptive research was conducted to design an electronic magazine based on Augmented Reality. The development process was carried out in two stages, namely analysis and design. The analysis phase was carried out by observation using a questionnaire and the design phase was carried out by utilizing various computer software. The result of this research was an e-magazine design that is integrated with Augmented Reality, so that students can see abstract biological objects by 3D Augmented Reality directly with the technology. These results are expected to be developed and conduct further testing